Intraoperative Radiation Therapy: A Promising Treatment Modality in Head and Neck Cancer - Hilal, Lara; Al Feghali, Karine A.; Ramia, Paul; Abu Gheida, Ibrahim; Obeid, Jean-Pierre; Jalbout, Wassim; Youssef, Bassem; Geara, Fady; Zeidan, Youssef H. (Frontiers in Oncology, 2017)
Every year almost 62,000 are diagnosed with a head and neck cancer and 13000 will succumb to their disease. In the primary setting intraoperative radiation therapy (IORT) can be used as a boost in select patients in order to optimize local control. Addition of external beam radiation to limited volumes results in improved disease control over surgery and IORT alone. In the recurrent setting, IORT can improve outcomes from salvage surgery especially in patients previously treated with external beam radiation. The use of IORT remains limited to select institutions with various modalities being currently employed including orthovoltage, electrons, and HDR- brachytherapy. Practically, execution of IORT requires a coordinated effort and careful planning by a multidisciplinary team involving the head and neck surgeon, radiation oncologist and physicist. The current review summarizes common uses, outcomes, toxicities and technical aspects of IORT in head and neck cancer patients.